Early antibiotics administration reduces mortality in sepsis patients in tertiary care hospital - Suramath Isaranuwatchai; Jirawat Buppanharun; Thamonwan Thongbun; Kaewklao Thavornwattana; Monprach Harnphadungkit; Taweegrit Siripongboonsitti (BMC Infectious Diseases)
Abstract Introduction Early antibiotic administration is one of the core treatments of sepsis which associated with reduced mortality rate. However, the appropriate timing of antibiotics remains a controversial issue, especially in patients without septic shock. Here, we reported the outcomes of early antibiotic administration within one hour from the time of infection suspicion in a tertiary care hospital. Methods We reviewed the medical records and sepsis protocols in Chulabhorn Hospital, Bangkok, Thailand, from January 2021 to December 2023 for patients presenting with sepsis. We had our own sepsis protocol which we used for early detection and treatment of sepsis patients. We compared the 28-day mortality, 90-day mortality, and the length of stay between patients with time-to-antibiotics (TTA) within one hour and patients with TTA more than one hour. Results We recruited 1,506 patients into our study. The mean age is 68 years and 49.40% of patients is female. 90.97% of the patients have comorbidities. The most common comorbidities were cancer (68.66%), and hypertension (33.40%). The 28-day mortality rate and the 90-day mortality rate were significantly lower in the patients with TTA within one hour compared to those with TTA more than one hour (P = 0.009 and P = 0.042, respectively). Nonetheless, adjusted mortality rate was significantly lower in only 28-day mortality rate but not 90-day mortality rate. Subgroup analysis showed that the mortality rate was significantly lower in patients with ICD-10 diagnosis of infections (15.35% vs. 21.51%, P = 0.029), patients with cancer (17.29% vs. 24.11%, P = 0.016), and patients with solid cancer (20.86% vs. 28.18%, P = 0.036). However, subgroup analysis for the mortality rate at 90 days were not statistically significant. Conclusion Antibiotic administration within one hour from the time of infection suspicion is associated with lower mortality rates at 28 days but not at 90 days after adjusted analysis. Cancer patients, especially patients with solid cancer, will benefit more with time-to-antibiotics less than one hour.